How to draw fairies in simple steps - Davies, Paul Bryn Davies (Tunbridge Wells, Kent Search Press, 2009)
Even complete beginners can create great drawings with this simple step-by-step guide. There is so much here to inspire more experienced artists too, with different styles including fun cartoons
Drawing
1
Keywords: Fairies in art; Drawing -- Technique